A METHOD FOR DYEING POLYESTER FIBRES WITH QUINONE DERIVATIVES AND EVALUATION OF THEIR ANTIOXIDANT ACTIVITY - (:unkn) unknown (ASSOC CHEMICAL ENG, 2018)
In this study, a series of bis(thio) substituted-1,4-naphthoquinone compounds (4a-j) were synthesized via Michael addition reaction and their structures were determined by infrared spectrometry, H-1 and C-13 nuclear magnetic resonance spectroscopy, mass spectrometry and elemental analysis. The synthesized substances were applied to polyester fibers and the dyeing properties were investigated. The rubbing fastness, wash fastness and optical properties of synthesized compounds were also studied. The color change and staining test results were found to be 4 to 4-5 for the most of the dyed samples. There is only a small number of previous studies interested with dyeing properties of synthetic derivatives of heteroatom-substituted-1,4-naphthoquinone compounds in existing literature. The synthesized dyes were screened for their antioxidant activity, using the CUPRAC method against trolox (TR) as the standard reference compound at room temperature. The aims of this study were the synthesis of the quinone compounds, the investigation of the capability of dyeing polyester fibers and the evaluation of their antioxidant capacity, using the CUPRAC method. The dyed polyester fibers are promising candidates for biologically active fabrics to be used in various ways. We were encouraged to do this study in order to determine the dying properties and antioxidant activities of the quinone compounds.
Keywords: 1,4-naphthoquinone dyes; disperse dyestuffs; dyeing; CUPRAC antioxidant assay; 1,4-NAPHTHOQUINONES; CAPACITY; DYES